Identifying issues and challenges in industrial training among Psychology undergraduates - Hamdan, Iman Najihah; Abd Rahman, Shukran (DergiPark, 2020)
Among the initiatives to provide effective all-encompassing learning experience is by including internship or industrial training programmes for undergraduates. While it is expected to equip students with important work-related skills, it too could result in negative impacts if it is not being properly managed. This article presents the findings of a study which identified issues and challenges faced by Psychology undergraduates in Malaysia while completing their industrial training. Using qualitative research design, the study gathered information from nine participants who responded to standardized open-ended interviews. 11 major themes, categorised in three different issues and challenges have been identified, namely departmental-related, workplace/organisational-related and personal-related matters. The findings are expected to help scope the underlying issues and challenges of industrial training programme in local universities. The findings can inform the context of each problem which can be further understood and acknowledged by university officials, useful for them to design necessary interventions such as workshops to discuss the ways to improve industrial training system for university students.